Review Of Intrusion Detection System In Various E-Commerce Platforms - Nafees, Shabeena; Pandey, Anil Kumar; Verma, Satya Bhushan (Journal of Neonatal Surgery, 2025)
The twenty-first century has witnessed a rapid growth of technological advancements aiming to lead the world towards a new era of innovations. E-commerce is a phenomenal product of this innovatory stream, and its influence extends far beyond traditional retail. The application circle of e-commerce is widespread in almost every sector of our life, including areas such as healthcare, finance, education, and more, proving its validity and impact on our routine life vividly. E-commerce communications depend on modern devices such as laptops, personal computers, communication sensors, servers, switches, etc. The expanding domain of e-commerce applications is bringing the involvement of more communication devices, which raises a serious question about the security of the whole communication system. Integrating suspicious entities with the mainstream communication network may create malicious activities resulting in severe outcomes. Hence, we need a secure communication framework to ensure attack-efficient and reliable communication streams, especially in critical sectors like healthcare, where data privacy and system integrity are paramount. This paper reviews different efficient and secure electronic payment systems, with an emphasis on their application across various sectors, including healthcare, Supply chain.